Nanoscale Modification of Titanium Implants Improves Behaviors of Bone Mesenchymal Stem Cells and Osteogenesis In Vivo. (4th January 2022) - Li, Huangdi; Huang, Jinghui; Wang, Yanpeng; Chen, Ziyuan; Li, Xing; Wei, Qiuping; Liu, Xifeng; Wang, Zi; Wen, Bin; Zhao, Yuetao; Liu, Jing; Zuo, Jun
Abstract : The surficial micro/nanotopography and physiochemical properties of titanium implants are essential for osteogenesis. However, these surface characters' influence on stem cell behaviors and osteogenesis is still not fully understood. In this study, titanium implants with different surface roughness, nanostructure, and wettability were fabricated by further nanoscale modification of sandblasted and acid-etched titanium (SLA: sandblasted and acid-etched) by H2 O2 treatment (hSLAs: H2 O2 treated SLA). The rat bone mesenchymal stem cells (rBMSCs: rat bone mesenchymal stem cells) are cultured on SLA and hSLA surfaces, and the cell behaviors of attachment, spreading, proliferation, and osteogenic differentiation are further analyzed. Measurements of surface characteristics show hSLA surface is equipped with nanoscale pores on microcavities and appeared to be hydrophilic. In vitro cell studies demonstrated that the hSLA titanium significantly enhances cell response to attachment, spreading, and proliferation. The hSLAs with proper degree of H2 O2 etching (h1SLA: treating SLA with H2 O2 for 1 hour) harvest the best improvement of differentiation of rBMSCs. Finally, the osteogenesis in beagle dogs was tested, and the h1SLA implants perform much better bone formation than SLA implants. These results indicate that the nanoscale modification of SLA titanium surface endowing nanostructures, roughness, and wettability could significantly improve the behaviors of bone mesenchymal stem cells and osteogenesis on the scaffold surface. These nanoscale modified SLA titanium scaffolds, fabricated in our study with enhanced cell affinity and osteogenesis, had great potential for implant dentistry.